2018
DOI: 10.1088/1361-6560/aadf29
|View full text |Cite
|
Sign up to set email alerts
|

Fano cavity test for electron Monte Carlo transport algorithms in magnetic fields: comparison between EGSnrc, PENELOPE, MCNP6 and Geant4

Abstract: A Fano cavity test was performed for four general-purpose Monte Carlo codes, EGSnrc, PENELOPE, MCNP6 and Geant4 to evaluate the accuracy of their electron transport algorithms in magnetic fields. In the simulations, a plane-parallel ionization chamber was modelled as a circular gas disk sandwiched between two circular solid wall disks. It was assumed that an isotropic and uniform line source per unit mass along the central axis of the gas and solid emits mono-energetic electrons with energies 0.01, 0.1, 1.0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In that work, it was recommended that EM ESTEPE, the parameter which limits the step size to ensure that the change in the direction of motion induced by the magnetic field is less than the set fractional value, should be set to 0.2. Recently, Lee et al . have found that the EGSnrc enhanced electric and magnetic field macros, which are used in this study, achieved the best accuracy in ion chamber Fano tests when compared to the magnetic field transport of PENELOPE, Geant4, and MCNP6.…”
Section: Resultsmentioning
confidence: 99%
“…In that work, it was recommended that EM ESTEPE, the parameter which limits the step size to ensure that the change in the direction of motion induced by the magnetic field is less than the set fractional value, should be set to 0.2. Recently, Lee et al . have found that the EGSnrc enhanced electric and magnetic field macros, which are used in this study, achieved the best accuracy in ion chamber Fano tests when compared to the magnetic field transport of PENELOPE, Geant4, and MCNP6.…”
Section: Resultsmentioning
confidence: 99%
“…First, the TOPAS Monte Carlo model of the brachytherapy source was verified by comparing calculated TG43 parameters with data from the literature. Second, this work relies on the accuracy of Geant4 toolkit to model transport of charged particles in magnetic fields, which has been already shown experimentally [7,38,39] and theoretically [40,41]. Third, we relied on the TOPAS tool for the implementation of magnetic field, DICOM patient, detailed geometry and source of the brachytherapy seed, and scoring.…”
Section: Discussionmentioning
confidence: 99%
“…It applies the adaptive multipoint integration algorithm, and allows for proper boundary crossing. Lee et al reported that EGSnrc with the EEMF macros achieved the highest accuracy for the Fano cavity test under the field strengths of 0.35, 1.0, 1.5, and 3.0 T, compared with the MC codes of PENELOPE, MCNP6, and Geant4.…”
Section: Methodsmentioning
confidence: 99%
“…It applies the adaptive multipoint integration algorithm, and allows for proper boundary crossing. Lee et al 29 reported that EGSnrc with the EEMF macros achieved the highest accuracy for the Fano cavity test under the field strengths of 0.35, 1.0, 1.5, and 3.0 T, compared with the MC codes of PENELOPE, MCNP6, and Geant4. The depth parameter of the RGD was set to 1 cm, d max (depth of the maximum dose), 5, 10, 15, 20, and 25 cm for a 10 cm 9 10 cm field at the detector center in a solid water phantom (RMI-457, q = 1.042 g/cm 3 GAMMEX, USA), with the dimensions of 30 cm 9 30 cm 9 30 cm.…”
Section: B1 Rgd Relative Responsementioning
confidence: 99%